2016
DOI: 10.1002/gj.2859
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb zircon age, geochemical and isotopic characteristics of the Miaoya syenite and carbonatite complex, central China

Abstract: The Miaoya syenite and carbonatite complex is located in the southern margin of the South Qinling belt, central China. LA‐ICP‐MS zircon U–Pb dating reveals that the syenite and carbonatite have crystallization ages of 445.2 ± 2.6 Ma (MSWD = 0.66) and 434.3 ± 3.2 Ma (MSWD = 1.08), respectively. Both syenite and carbonatite display low ISr values (0.7004 to 0.7053) and depleted εNd(t) values of +1.1 to +5.5, with one‐stage Nd model ages of 0.65 to 0.94 Ga. Their zircon εHf(t) values are also similarly positive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 67 publications
(119 reference statements)
1
9
0
Order By: Relevance
“…volcanic rocks of the Yaolinghe Group), we speculated that the so-called "syenites" samples in Xu et al (2014) could be xenoliths of the country rocks (particularly that the Miaoya complex contains 2.5 vol% xenoliths). For the carbonatites, Zhu et al (2016) and Ying et al 2017obtained similar zircon ages of ~430 Ma. This age should be reliable as these zircon grains are characterized by low U and high Th/U ratios, similar to zircons crystallized from carbonatitic magmas (Yuan et al, 2008).…”
Section: Ree Mineralization In the Miaoya Complexmentioning
confidence: 79%
See 2 more Smart Citations
“…volcanic rocks of the Yaolinghe Group), we speculated that the so-called "syenites" samples in Xu et al (2014) could be xenoliths of the country rocks (particularly that the Miaoya complex contains 2.5 vol% xenoliths). For the carbonatites, Zhu et al (2016) and Ying et al 2017obtained similar zircon ages of ~430 Ma. This age should be reliable as these zircon grains are characterized by low U and high Th/U ratios, similar to zircons crystallized from carbonatitic magmas (Yuan et al, 2008).…”
Section: Ree Mineralization In the Miaoya Complexmentioning
confidence: 79%
“…3f). Xu et al (2014) has obtained zircon ages of Ma for the syenites, but such ages were suggested to be unreliable by Zhu et al (2016) and Ying et al (2017) who both obtained a similar zircon age of Ma for the syenites. Considering that an age of 766 Ma is comparable to those of the country rocks (i.e.…”
Section: Ree Mineralization In the Miaoya Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Two carbonatite-alkaline complexes with low-grade REE mineralization, the Miaoya and Shaxiongdong complex, South Qinling Belt of Central China, were selected to evaluate their REE mineralization histories in this study. Both complexes have zircon U-Pb ages of 440-430 Ma, which have been interpreted as intrusive ages (Xu et al 2008;Ying et al 2017;Zhu et al 2017;Chen et al 2018;Su et al 2019). However, previous studies also reported monazite ages of ~230 Ma, which has been interpreted as either an independent REE mineralization (Xu et al 2014) or an REE remobilization event (Ying et al 2017;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Burmakina & Tsygankov, 2013; Mingram, Trumbull, Littman, & Gerstenberger, 2000; Vernikovsky et al, 2003); and (vii) fractional crystallization (with or without crustal assimilation) of mantle‐derived magmas (e.g. Litvinovsky et al, 2002; Mingram et al, 2000; Riishuus et al, 2005; Zhu et al, 2017). The petrogenesis of syenite remains a subject of considerable controversy, and some models are in direct conflict with the results of experimental studies.…”
Section: Introductionmentioning
confidence: 99%